Question

( # quad ) St ( quad x^{2}+2 x^{3}-3 x^{2}+2 x-1=0 quad ) has ( 4 operatorname{ros} theta )
( a_{1}, a_{2}, a_{3}, a_{4} )
they ( x^{4}+2 x^{3}-3 x^{2}+2 x-1=(x-9)left(x-a_{2}right)left(x-a_{3}right)left(x-a_{4}right) )
( therefore ) to finder the value of (-9,1)( left(2-a_{2}right)left(2-a_{3}right)left(2-a_{4}right) )
All we neted to do is plug ( x=2 ) in ( x^{64}+2 x^{3}-3 x^{2}+2 x-1 ) ( =2^{4}+2 times 2^{3}-3 times 2^{2}+2 times 2-1 )
( =16+16-12+4-1 )
( =23 )

# 8) If the roots of the equation x4 + 2x3 -3x2+2x-1=0 are a,, az, az, a, then find (2-a) (2-a) (2-3) (2-2)

Solution